2021
DOI: 10.3847/1538-4357/abf6c7
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Discontinuity Transformation at the Bow Shock

Abstract: Solar wind plasma at the Earth’s orbit carries transient magnetic field structures including discontinuities. Their interaction with the Earth’s bow shock can significantly alter discontinuity configuration and stability. We investigate such an interaction for the most widespread type of solar wind discontinuities—rotational discontinuities (RDs). We use a set of in situ multispacecraft observations and perform kinetic hybrid simulations. We focus on the RD current density amplification that may lead to magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 135 publications
0
8
1
Order By: Relevance
“…Moreover, we find that the ID occurrence rate in the magnetosheath is quite lower than in the solar wind, which seems contradictory to the fact that many studies have demonstrated MHD turbulence can generate IDs, and plasmas become more turbulent crossing the bow shock (Greco et al 2008(Greco et al , 2009Borovsky 2010;Zhdankin et al 2012). One possible explanation is that the bow shock alters the IDs' stability and makes them dissipate (Kropotina et al 2021). It can also explain the two-exponential distribution of the field rotation angles of the IDs in the magnetosheath.…”
Section: Conclusion and Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Moreover, we find that the ID occurrence rate in the magnetosheath is quite lower than in the solar wind, which seems contradictory to the fact that many studies have demonstrated MHD turbulence can generate IDs, and plasmas become more turbulent crossing the bow shock (Greco et al 2008(Greco et al , 2009Borovsky 2010;Zhdankin et al 2012). One possible explanation is that the bow shock alters the IDs' stability and makes them dissipate (Kropotina et al 2021). It can also explain the two-exponential distribution of the field rotation angles of the IDs in the magnetosheath.…”
Section: Conclusion and Discussioncontrasting
confidence: 76%
“…More recently, Liu et al (2021Liu et al ( , 2022 investigate, via the Parker Solar Probe mission (Fox et al 2016), the IDs in a previously unexplored region as close to the Sun as 0.13 au, and find an extreme abundance of RDs that may be related to the local turbulence therein and play an important role in accelerating particles in the pristine solar wind. The interaction of IDs with the terrestrial bow shock has also attracted much interest since it can significantly affect the near-Earth space environments (Koval et al 2005(Koval et al , 2006Omidi & Sibeck 2007;Samsonov et al 2007;Omidi et al 2010;Fu et al 2012a;Goncharov et al 2015;Kropotina et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bow shock and foreshock environments also significantly modify the current density within RDs (Kropotina et al., 2021). Crossing the bow shock can disrupt the reconnection exhausts and shut off the reconnection process within the RCS (Phan et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Kropotina et al. (2021) showed that the bow shock‐RD interaction may alter the properties of the RD, which in turn makes the RD unstable to magnetic reconnection. Nevertheless, it is often hard for space observations to conclude whether reconnection has taken place inside the discontinuity before or after it touches with the bow shock.…”
Section: Introductionmentioning
confidence: 99%
“…Hamrin et al (2019) suggested that reconnection can take place at the quasi-perpendicular (Q-𝐴𝐴 ⟂ ) bow shock because of the compression of a directional discontinuity at the bow shock. More recently, Kropotina et al (2021) showed that the bow shock-RD interaction may alter the properties of the RD, which in turn makes the RD unstable to magnetic reconnection. Nevertheless, it is often hard for space observations to conclude whether reconnection has taken place inside the discontinuity before or after it touches with the bow shock.…”
mentioning
confidence: 99%